Homogeneous positive electrode material, preparation method thereof and all-solid-state lithium ion battery
By designing the homogeneous positive electrode material Li2-xTi2 (GexP0.75S4-ySey)3, the interface incompatibility problem of heterogeneous positive electrode material is solved, the battery life is extended, and the lithium ion deintercalation kinetics and the battery's long cycle performance are improved.
Patent Information
- Application Number
- CN202411938393.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
In existing all-solid-state lithium-ion batteries, the interface incompatibility of heterogeneous positive electrode materials leads to slowing carrier transfer kinetics, shortening battery life, and the reaction between conductive additives and layered oxides reduces battery performance.
Using the homogeneous positive electrode material Li2-xTi2 (GexP0.75S4-ySey)3, by introducing Ge and Se elements, the electrochemically inactive additives were discarded, and a highly homogenized, high-stable, high-entropy positive electrode material was designed to eliminate heterogeneous interface side reactions and improve the deintercalation kinetics of lithium ions.
It extends the cycle life of the battery, improves the deintercalation kinetics of lithium ions, enhances the long cycle performance of the battery, avoids inter-particle shedding and internal cracking, and improves the overall performance of the battery.
Smart Images

Figure CN119742365A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a homogeneous positive electrode material for lithium ion batteries and a preparation method thereof, and an all-solid-state lithium ion battery. Background Art
[0002] After decades of rapid development, lithium-ion batteries have formed a huge market scale and become an indispensable part of our daily life. However, the pursuit of high-safety and high-energy-density lithium-ion batteries requires us to develop in the direction of all-solid-state batteries. All-solid-state lithium batteries use non-flammable solid electrolytes, which can meet people's growing demand for highly safe energy storage systems and are expected to become the mainstream path for electric vehicles and large-scale energy storage applications.
[0003] However, the most advanced all-solid-state lithium batteries usually use positive electrode active materials such as LiCoO2, LiNiO2 and their derivatives. Although these layered oxides have high energy density, they have poor carrier transport capabilities and lithium ion conductivity of 10 -7 ~10 -6 S cm -1 , the electronic conductivity is 10 -6 ~10 -4 S cm -1 In order to ensure sufficient Li + Extraction / insertion kinetics, a certain amount of conductive additives such as ionic solid electrolytes (20-40 wt%) and electronic carbonaceous materials (1-5 wt%) are essential in heterogeneous composite cathodes to construct efficient charge carrier migration pathways. However, the presence of additives can cause interfacial incompatibility issues.
[0004] Interfacial incompatibilities include space charge layers, chemical reactions, elemental interdiffusion, and electrolyte decomposition, which typically occur at the interface between conductive additives and layered oxides, creating a high-resistance phase that hinders carrier migration. In heterogeneous cathodes, lithium ions and electrons travel along tortuous conduction paths that increase the carrier migration barrier and slow down the carrier transport kinetics by 10 to 100 times. Worse still, the asynchronous electron / lithium ion transport severely limits the intercalation and deintercalation of lithium ions: because it typically occurs when electrons and lithium ions meet at the heterojunction of the cathode active material, any electron- and ion-conductive additives that cannot transport electrons from the current collector or Li from the electrolyte layer are unable to transport electrons. + Isolated conductive additive particles will significantly reduce the Li + In addition, these layered oxides have a high Young's modulus (about 180 GPa) and are +The large volume change (more than 2.6%) during the extraction / insertion process leads to inter-particle shedding and intra-particle cracking during continuous cycling, which in turn destroys the carrier transport path. Worse, the newly exposed parts of the active material caused by inter-particle shedding and intra-particle cracking will further react with the conductive additives, thereby degrading the battery performance.
[0005] In summary, the mechanochemical and electrochemical incompatibility between heterogeneous components significantly reduces the battery life, and the current mainstream modification strategy is still to introduce coating materials or additive materials on the positive electrode surface for optimization. This method does not fundamentally solve the problem of heterogeneous contact.
[0006] In view of this, this patent application is filed. Summary of the invention
[0007] In order to solve the problem of heterogeneous interface incompatibility that exists in the current method of introducing coating materials or additives on the positive electrode surface for optimizing positive electrode materials, the present invention provides a homogeneous positive electrode material for a lithium ion battery and a preparation method thereof, which solves the above-mentioned problem. The present invention also provides an all-solid-state lithium ion battery.
[0008] The present invention is achieved through the following technical solutions:
[0009] The first object of the present invention is to provide a positive electrode material, wherein the positive electrode material is a homogeneous positive electrode material, and the structural formula of the positive electrode material is Li 2-x Ti2(Ge x P 0.75 S 4-y Se y )3, where 0 <x<1,0<y<1。
[0010] In order to solve the technical bottleneck related to the heterogeneity of the positive electrode, the present invention is based on the ultrafast ion conductor solid electrolyte Li2Ti2(PS4)3, introduces the elements Ge and Se, and rationally designs the components of the positive electrode material, discards the electrochemically inactive additives, and obtains a highly homogenized, highly stable, high-entropy positive electrode material, which can eliminate the interface side reactions between heterogeneous components, thereby extending the cycle life of the battery. And the high homogenization of the material leads to linear and synchronous transmission of electrons and lithium ions, which can effectively improve the deintercalation kinetics of lithium ions, which is beneficial to improving power efficiency. At the same time, the material of the present invention can avoid inter-particle shedding and intra-particle cracking in continuous cycles, and the prepared all-solid-state lithium-ion battery has good long-cycle performance.
[0011] As a preferred design, 0.1≤x≤0.5, 0.1≤y≤0.4.
[0012] As a preferred design, x=0.25, y=0.2.
[0013] The second object of the present invention is to provide a method for preparing the positive electrode material described in any one of the above items, which is prepared using lithium sulfide, titanium sulfide, germanium sulfide, phosphorus sulfide and titanium selenide as raw materials.
[0014] As a preferred design, lithium sulfide, titanium sulfide, germanium sulfide, phosphorus sulfide and titanium selenide are weighed according to the ratio of each raw material;
[0015] The raw materials are ball-milled and pressed into particles;
[0016] The particles are mixed with sulfur and sealed, and then sintered in an inert environment to obtain a solid powder;
[0017] The obtained solid powder is ground and sieved to obtain the positive electrode material.
[0018] As a preferred design, the raw material is ball-milled at a rotation speed of 250-400 rpm for 24-48 hours.
[0019] As a preferred design, the ball-milled powder is placed in a spherical mold with a diameter of 12 mm and pressed into particles.
[0020] As a preferred design, during the sintering process, the sintering temperature is 350-750° C., the sintering time is 6-10 hours, and the sintering is naturally cooled to room temperature after sintering.
[0021] The third object of the present invention is to provide an all-solid-state lithium-ion battery using any of the above-mentioned positive electrode materials as raw materials.
[0022] As a preferred design, Li6PS5Cl powder is used as the electrolyte layer, the positive electrode material is located on the top of the electrolyte layer, and the Li-Si alloy negative electrode powder is located at the bottom of the electrolyte layer.
[0023] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0024] 1. The present invention optimizes the structure of the positive electrode material to make it have the additive properties of conductive and ion-conducting functions and the active material properties of lithium storage function, thus avoiding the heterogeneous interface contact problem between the active material and the additive;
[0025] 2. The interface compatibility between solid electrolyte and positive electrode materials has been optimized. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0027] Figure 1 This is a SEM image of the cross section of an all-solid-state battery prepared using the positive electrode material obtained in Example 1 of the present invention.
[0028] Figure 2 It is a long cycle data diagram of the lithium ion batteries of various embodiments and comparative examples. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0030] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0031] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0032] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0033] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0034] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0035] Embodiment 1:
[0036] Design a highly homogenized and stable high-entropy cathode material with the structural formula Li 1.75 Ti2(Ge 0.25 P 0.75 S 3.8 Se 0.2 )3. Where x = 0.25, y = 0.2.
[0037] A method for preparing a highly homogenized and highly stable high-entropy positive electrode material, specifically comprising the following steps:
[0038] Step 1: weigh lithium sulfide, titanium sulfide, germanium sulfide, phosphorus sulfide and titanium selenide according to molar ratio;
[0039] Step 2: Place all the materials weighed in step 1 into a zirconia ball mill and then ball mill at 300 rpm for 36 h;
[0040] Step 3: The powders obtained by ball milling in step 2 are placed in a 12 mm diameter spherical mold and pressed into granules;
[0041] Step 4: Mix the particles with appropriate sulfur and seal them in a quartz tube, and pass argon gas to ensure an inert environment. The sintering temperature is 500°C and the sintering time is 8 hours. After the sintering is completed, it is naturally cooled to room temperature.
[0042] Step 5: Take out the solid powder obtained in step 4 and grind it, and use a sieve to screen it to obtain a highly homogenized, highly stable, high-entropy positive electrode material of the target size.
[0043] The above-mentioned high entropy cathode material is used to prepare an all-solid-state lithium-ion battery. The specific preparation steps are:
[0044] Step S1: Pressing 100 mg Li6PS5Cl powder at 200 MPa as the electrolyte layer;
[0045] Step S2: Then 400 mg of the prepared sample powder was weighed and evenly added to the top of the electrolyte layer and compressed at 350 MPa;
[0046] Step S3: Add 60 mg of Li-Si alloy anode powder at the bottom of the Li6PS5Cl layer and compress at 350 MPa for 2 min;
[0047] Step S4: Place the laminated sheet in step S3 in a soft-pack packaging mold to obtain the desired all-solid-state battery.
[0048] The cross section of the all-solid-state battery prepared in this embodiment was characterized by SEM, and the obtained SEM image is as follows: Figure 1 As shown in the figure, it can be seen that the all-solid-state battery with distinct layers can be successfully prepared.
[0049] The electrochemical performance of the obtained all-solid-state battery was tested: a soft pack was used to test the electrochemical performance of the prepared battery, and a cyclic charge and discharge test was performed between 1.6V and 3.5V, with a current density of 2.5mA / cm -2 , cycle 5000 times, the charge and discharge test results are as follows Figure 2 shown.
[0050] Embodiment 2:
[0051] Design a highly homogenized and stable high-entropy cathode material with the structural formula Li 1.5 Ti2(Ge 0.5 P 0.75 S 3.6 Se 0.4 )3. Where x = 0.5, y = 0.4.
[0052] The specific preparation process includes the following steps:
[0053] Step 1: weigh lithium sulfide, titanium sulfide, germanium sulfide, phosphorus sulfide and titanium selenide according to molar ratio;
[0054] Step 2: Place all the materials weighed in step 1 into a zirconia ball mill and then ball mill at 300 rpm for 36 h;
[0055] Step 3: The powders obtained by ball milling in step 2 are placed in a 12 mm diameter spherical mold and pressed into granules;
[0056] Step 4: Mix the particles with appropriate sulfur and seal them in a quartz tube, and pass argon gas to ensure an inert environment. The sintering temperature is 500°C and the sintering time is 8 hours. After the sintering is completed, it is naturally cooled to room temperature.
[0057] Step 5: Take out the solid powder obtained in step 4 and grind it, and use a sieve to screen it to obtain a highly homogenized, highly stable, high-entropy positive electrode material of the target size.
[0058] The high entropy cathode material is used to prepare an all-solid-state lithium-ion battery. The specific preparation process is the same as in Example 1.
[0059] The electrochemical performance of the obtained all-solid-state battery was tested: a soft pack was used to test the electrochemical performance of the prepared battery, and a cyclic charge and discharge test was performed between 1.6V and 3.5V, with a current density of 2.5mA / cm -2 , cycle 5000 times, the charge and discharge test results are as follows Figure 2 shown.
[0060] Embodiment 3:
[0061] A highly homogenized and stable high-entropy cathode material with the structural formula Li 1.9 Ti2(Ge 0.1 P 0.75 S 3.9 Se 0.1 )3. Where x=0.1, y=0.1.
[0062] The specific preparation process includes the following steps:
[0063] Step 1: weigh lithium sulfide, titanium sulfide, germanium sulfide, phosphorus sulfide and titanium selenide according to molar ratio;
[0064] Step 2: Place all the materials weighed in step 1 into a zirconia ball mill and then ball mill at 300 rpm for 36 h;
[0065] Step 3: The powders obtained by ball milling in step 2 are placed in a 12 mm diameter spherical mold and pressed into granules;
[0066] Step 4: Mix the particles with appropriate sulfur and seal them in a quartz tube, and pass argon gas to ensure an inert environment. The sintering temperature is 500°C and the sintering time is 8 hours. After the sintering is completed, it is naturally cooled to room temperature.
[0067] Step 5: Take out the solid powder obtained in step 4 and grind it, and use a sieve to screen it to obtain a highly homogenized, highly stable, high-entropy positive electrode material of the target size.
[0068] The high entropy cathode material is used to prepare an all-solid-state lithium-ion battery. The specific preparation process is the same as in Example 1.
[0069] The electrochemical performance of the obtained all-solid-state battery was tested: a soft pack was used to test the electrochemical performance of the prepared battery, and a cyclic charge and discharge test was performed between 1.6V and 3.5V, with a current density of 2.5mA / cm -2 , cycle 5000 times, the charge and discharge test results are as follows Figure 2 shown.
[0070] Comparative Example 1:
[0071] A highly homogenized and stable high-entropy cathode material with the structural formula Li 1.75 Ti2(Ge 0.25 P 0.75 Se4)3. Wherein, x=0.25, y=0.
[0072] The specific preparation process includes the following steps:
[0073] Step 1: weigh lithium sulfide, titanium sulfide, germanium sulfide, phosphorus sulfide and titanium selenide according to molar ratio;
[0074] Step 2: Place all the materials weighed in step 1 into a zirconia ball mill and then ball mill at 300 rpm for 36 h;
[0075] Step 3: The powders obtained by ball milling in step 2 are placed in a 12 mm diameter spherical mold and pressed into granules;
[0076] Step 4: Mix the particles with appropriate sulfur and seal them in a quartz tube, and pass argon gas to ensure an inert environment. The sintering temperature is 500°C and the sintering time is 8 hours. After the sintering is completed, it is naturally cooled to room temperature.
[0077] Step 5: Take out the solid powder obtained in step 4 and grind it, and use a sieve to screen it to obtain a highly homogenized, highly stable, high-entropy positive electrode material of the target size.
[0078] The positive electrode material obtained in the above comparative example 1 is used to prepare an all-solid-state lithium-ion battery. The specific preparation process is the same as that in example 1.
[0079] The electrochemical performance of the obtained all-solid-state battery was tested: a soft pack was used to test the electrochemical performance of the prepared battery, and a cyclic charge and discharge test was performed between 1.6V and 3.5V, with a current density of 2.5mA / cm -2 , cycle 5000 times, the charge and discharge test results are as follows Figure 2 shown.
[0080] Comparative Example 2:
[0081] A highly homogenized and stable high-entropy cathode material with the structural formula Li 1.75 Ti2(P 0.75 S 3.8 Se0.2 )3. Where x = 0, y = 0.2. The rest of the steps are exactly the same.
[0082] The preparation process of the positive electrode material is the same as that of Example 1.
[0083] The positive electrode material obtained in the above comparative example 2 is used to prepare an all-solid-state lithium-ion battery. The specific preparation process is the same as that of example 1.
[0084] The electrochemical performance of the obtained all-solid-state battery was tested: a soft pack was used to test the electrochemical performance of the prepared battery, and a cyclic charge and discharge test was performed between 1.6V and 3.5V, with a current density of 2.5mA / cm -2 , cycle 5000 times, the charge and discharge test results are as follows Figure 2 shown.
[0085] Comparative Example 3:
[0086] A highly homogenized and stable high-entropy cathode material with the structural formula Li 0.8 Ti2(G 1.2 P 0.75 S 3.8 Se 0.2 )3. Where x=1.2, y=0.2.
[0087] The preparation process of the positive electrode material is the same as that of Example 1.
[0088] The positive electrode material obtained in the above comparative example 3 is used to prepare an all-solid-state lithium-ion battery. The specific preparation process is the same as that in Example 1.
[0089] The electrochemical performance of the obtained all-solid-state battery was tested: a soft pack was used to test the electrochemical performance of the prepared battery, and a cyclic charge and discharge test was performed between 1.6V and 3.5V, with a current density of 2.5mA / cm -2 , cycle 5000 times, the charge and discharge test results are as follows Figure 2 shown.
[0090] Comparative Example 4:
[0091] A highly homogenized and stable high-entropy cathode material with the structural formula Li 1.75 Ti2(P 0.75 S 2.8 Se 1.2 )3. Where x = 0.25, y = 1.2.
[0092] The preparation process of the positive electrode material is the same as that of Example 1.
[0093] The positive electrode material obtained in the above comparative example 4 is used to prepare an all-solid-state lithium-ion battery. The specific preparation process is the same as that in Example 1.
[0094] The electrochemical performance of the obtained all-solid-state battery was tested: a soft pack was used to test the electrochemical performance of the prepared battery, and a cyclic charge and discharge test was performed between 1.6V and 3.5V, with a current density of 2.5mA / cm -2 , cycle 5000 times, the charge and discharge test results are as follows Figure 2 shown.
[0095] Depend on Figure 2 The long cycle data graphs of the all-solid-state lithium-ion batteries obtained from the various embodiments and comparative examples show that embodiments 1 to 3 exhibit good capacity characteristics and long cycle life by rationally designing the structural formula of the positive electrode material. For example, after the battery in embodiment 1 has undergone 5000 cycles of long cycles, the discharge capacity of the battery is 168 mAh / g. After 5000 cycles of long cycles, the discharge capacity of the battery in embodiment 3 remains at around 110 mAh / g. In comparative examples 1 and 2, Ge and Se are added separately, respectively. When Ge is introduced alone, the capacity is lower, but the life is more stable. When Se is introduced alone, the capacity is slightly higher but decays faster. Comparative examples 3 and 4 are the excessive introduction of Ge and Se, respectively, reflecting the inhibitory effect of excessive introduction on material properties.
[0096] The positive electrode material obtained by the present invention has the following technical advantages:
[0097] 1. The additives with conductive and ion-conducting functions and the active materials with lithium storage functions are integrated into one, avoiding the heterogeneous interface contact problem between the active materials and the additives, eliminating the interface side reactions between the heterogeneous components, and thus extending the cycle life of the battery;
[0098] 2. The interface compatibility problem between solid electrolyte and positive electrode materials has been optimized. The high homogenization of the material leads to linear and synchronous transmission of electrons and lithium ions, which can effectively improve the deintercalation and insertion kinetics of lithium ions.
[0099] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A homogeneous positive electrode material for a lithium ion battery, characterized in that: The positive electrode material is a homogeneous positive electrode material, and the structural formula of the positive electrode material is Li 2-x Ti2(Ge x P 0.75 S 4-y Se y )3, where 0 <x<1,0<y<1。 2. A homogeneous positive electrode material for lithium ion batteries according to claim 1, characterized in that: 0.1≤x≤0.5, 0.1≤y≤0.
4.
3. The homogeneous positive electrode material for lithium ion battery according to claim 1, characterized in that: x=0.25, y=0.
2.
4. The method for preparing a homogeneous positive electrode material for a lithium ion battery according to any one of claims 1 to 3, characterized in that: It is prepared using lithium sulfide, titanium sulfide, germanium sulfide, phosphorus sulfide and titanium selenide as raw materials.
5. The method for preparing a homogeneous positive electrode material for a lithium ion battery according to claim 4, characterized in that: Weigh lithium sulfide, titanium sulfide, germanium sulfide, phosphorus sulfide and titanium selenide according to the ratio of each raw material; The raw materials are ball-milled and pressed into particles; The particles are mixed with sulfur and sealed, and then sintered in an inert environment to obtain a solid powder; The obtained solid powder is ground and sieved to obtain the positive electrode material.
6. The method for preparing a homogeneous positive electrode material for a lithium ion battery according to claim 5, characterized in that: The raw materials are ball-milled at a speed of 250-400 rpm for 24-48 hours.
7. The method for preparing a homogeneous positive electrode material for a lithium ion battery according to claim 5, characterized in that: The ball-milled powder was placed in a spherical mold with a diameter of 12 mm and pressed into granules.
8. The method for preparing a homogeneous positive electrode material for a lithium ion battery according to claim 5, characterized in that: During the sintering process, the sintering temperature is 350-750° C., the sintering time is 6-10 hours, and the sintering is naturally cooled to room temperature after sintering.
9. An all-solid-state lithium-ion battery, characterized in that: The homogeneous positive electrode material prepared by the method according to any one of claims 1 to 3 or any one of claims 4 to 8 is used as the raw material.
10. The all-solid-state lithium-ion battery according to claim 9, characterized in that: Li6PS5Cl powder is used as the electrolyte layer, the positive electrode material is located on the top of the electrolyte layer, and the Li-Si alloy negative electrode powder is located at the bottom of the electrolyte layer.
Citation Information
Patent Citations
Sulfo-lithium ion superconductor based on selenium doping and preparation method thereof
CN104779375A
Graphene-coated titanium niobium oxide composite electrode material, lithium primary battery and preparation method thereof
CN109167049A
Niobium pentoxide coated graphite composite negative electrode material and preparation method thereof
CN114864916A
Oxide-promoted reversible sulfenyl positive electrode and preparation method thereof
CN118299532A